Fatigue, treatment satisfaction and health‐related quality of life among patients receiving novel drugs suppressing androgen signalling for the treatment of metastatic castrate‐resistant prostate cancer. (8th November 2018) - Dearden, Lindsay; Shalet, Natalie; Artenie, Cristiana; Mills, Andrew; Jackson, Claire; Grant, Laura; Gater, Adam
Abstract: Clinical studies have demonstrated the benefits of abiraterone acetate + prednisone (AAP) and enzalutamide (ENZ) in significantly improving survival among metastatic castration‐resistant prostate cancer (mCRPC) patients. However, evidence regarding patient's real‐world experience, particularly with respect to fatigue, treatment satisfaction and health‐related quality of life (HRQoL) is limited. Interviews were initially conducted with patients ( n  = 38) and carers ( n  = 12) to elicit qualitative data regarding their experiences. Findings informed the design of a quantitative, multinational online survey of mCRPC patients ( n  = 152) receiving AAP or ENZ. Participants completed validated questionnaires assessing fatigue (Brief Fatigue Inventory), treatment satisfaction (Cancer Therapy Satisfaction Questionnaire) and HRQoL (EuroQol‐5‐Dimensions). Results indicated that patients were generally satisfied with these therapies, more specifically with reductions in prostate‐specific antigen levels and extended survival. Fatigue was commonly linked to poor HRQoL and responses indicated that significantly fewer patients in the AAP group reported feeling usually tired or fatigued in the last week compared to the ENZ group (33% vs. 55%, p  = 0.006 respectively). Findings highlight the benefit of AAP and ENZ in promoting the "quality" of extended survival. That fatigue was lower among patients receiving AAP may be important for informing treatment decisions. Further research is needed to gain deeper insights.